Assam : Health Policy Note - World Bank (Washington, DC, 2013)
The population of Assam is 26.64 million (2001), more than 85% of which live in rural areas. The state is one of the poorer states in the country, with an estimated GDP per capita equal to Rs. 12,163, which is less than two thirds of the national average (2001-02). Growth in the 1980-90s has been one of the lowest in the country (just above 1 percent real per capita growth), although the economic situation is reported to have improved in more recent years. The economy is predominantly rural (40 percent of Net State Domestic Product is from agriculture, and 74 percent of the population is engaged in agriculture), and it is heavily dependent on the tea estate sector (800 tea gardens that produce 15% of the world tea). The non-agricultural principal activity is oil and gas extraction and transformation (there are two oil refineries in the North-Eastern part of the state, plus a third one is under construction). Population below poverty line is estimated to be 36 percent, scheduled caste 7.4 percent and scheduled tribe 12.8 percent of the total population.